Development and implementation of an open source quadruped robot (2025)
This work presents an open-source quadruped robot, Naranjelio, featuring a 3Dprinted structure, cost-effective servo motors, and an onboard IMU and Raspberry Pi for real-time feedback. A ROS2-based control environment enables motion generation, data logging, and user interaction, while an Isaac Sim integration supports reinforcement learning exploration. A key contribution is the Quadruped Gait (E)Stability (QGE) metric, which combines acceleration and angular velocity data to yield a 0-1 gait quality score. Experimental results demonstrate Naranjelio's ability to carry payloads up to 66% of its own mass, though with reduced range of motion. Crucially, QGE quantifies these performance trade-offs, guiding iterative refinements in both structure and control for more robust, reliable gait.